Proposição de roteiro para implantação de gestão do conhecimento aplicada ao suporte técnico e atendimento a clientes - Statdlober, Juliano (Universidade do Vale do Rio dos Sinos, 2017)
This paper aims to propose a roadmap for deployment of Knowledge Management in technical support and customer care areas of companies. Some important challenges are present for this area, asBR large and diversified amount of complex environments and existing technologies, with fast technological evolution, demanding permanent knowledge updating for people involved in attention to users. Those difficulties and challenges suggest that Knowledge management could bring great benefits, if properly deployed. The proposed roadmap is based on internationally recognized methodologies and best practices and is validated in a software company that is a national reference in its area.
Keywords: Implantação da gestão; Áreas de suporte técnico; Usuários; Roteiro; Implementation of management; Technical support a areas; Users; Script